2012
DOI: 10.3182/20120829-3-hu-2029.00033
|View full text |Cite
|
Sign up to set email alerts
|

Traversing the Fuzzy Valley: Problems Caused by Reliance on Default Simulation and Parameter Identification Programs for Discontinuous Models

Abstract: The Levenberg-Marquardt parameter identification method is often used in tandem with numerical Runge-Kutta model simulation to find optimal model parameter values to match measured data. However, these methods can potentially find erroneous parameter values. The problem is exacerbated when discontinuous models are analyzed.A highly parameterized respiratory mechanics model defines a pressure-volume response to a low flow experiment in an acute respiratory distress syndrome patient. Levenberg-Marquardt paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Such methods are typically effective for objective surfaces that are well conditioned, but can result in excessive computational cost or failed convergence when this is not the case. In particular, use of gradient descent methods for models with significant parameter tradeoff effects can lead to premature termination (Docherty et al, 2013, Docherty et al, 2012c, Docherty et al, 2012a. It has been shown that in such models, the premature termination most often occurs on the major axes of the objective surface contours (that are often elliptical).…”
Section: Introductionmentioning
confidence: 99%
“…Such methods are typically effective for objective surfaces that are well conditioned, but can result in excessive computational cost or failed convergence when this is not the case. In particular, use of gradient descent methods for models with significant parameter tradeoff effects can lead to premature termination (Docherty et al, 2013, Docherty et al, 2012c, Docherty et al, 2012a. It has been shown that in such models, the premature termination most often occurs on the major axes of the objective surface contours (that are often elliptical).…”
Section: Introductionmentioning
confidence: 99%